Information problem-solving skills training with flipped methodology in a virtual environment - García, Consuelo; Argelagós, Esther; Privado, Jesús (ICERI Proceedings, 2020)
The need to solve information problems is a constant in the academic field. Most Higher Education students are extremely competent using Internet and social networks and really skilled in the use of smart phones. However, their ability to manage digital information for academic purposes is much more limited since they lack the necessary critical thinking and ability to search and select information relevant to their academic tasks. This research aims to show how 50 students from the Faculty of Education of the Universidad Internacional de la Rioja (UNIR) were trained using flipped methodology in a virtual environment. The students used a material that included video modelling examples, tasks performed and tasks to be performed. After the resolution of each task, training sessions were held with the instructors to offer feedback on each task. Training was based on the IPS model by Brand-Gruwel, Wopereis and Vermetten (2015). The results showed an improvement in their skills to solve information problems in a pre-post test situation and high satisfaction.
Ponencia de la conferencia "12th Annual International Conference of Education, Research and Innovation (ICERI)", Seville, Spain.
Keywords: training; higher education; flipped methodology; information problem-solving skills; WOS(2)